Recent Trends in the Pretreatment of Lignocellulosic Biomass for Value-Added Products - Baruah, Julie; Nath, Bikash Kar; Sharma, Ritika; Kumar, Sachin; Deka, Ramesh Chandra; Baruah, Deben Chandra; Kalita, Eeshan (Frontiers in Energy Research, 2018)
Lignocellulosic biomass (LCB) is the most abundantly available bioresource amounting to about a global yield of up to 1.3 billion tons per year. The hydrolysis of LCB results in the release of various reducing sugars which are highly valued in the production of biofuels such as bioethanol and biogas, various organic acids, phenols, and aldehydes. The majority of LCB is composed of biological polymers such as cellulose, hemicellulose and lignin, which are strongly associated with each other by covalent and hydrogen bonds thus forming a highly recalcitrant structure. The presence of lignin renders the bio-polymeric structure highly resistant to solubilization thereby inhibiting the hydrolysis of cellulose and hemicellulose which presents a significant challenge for the isolation of the respective bio-polymeric components. This has led to extensive research in the development of various pretreatment techniques utilizing various physical, chemical, physicochemical and biological approaches which are specifically tailored towards the source biomaterial and its application. The objective of this review is to discuss the various pretreatment strategies currently in use and provide an overview of their utilization for the isolation of high-value bio-polymeric components. The article further discusses the advantages and disadvantages of the various pretreatment methodologies as well as addresses the role of various key factors that are likely to have a significant impact on the pretreatment and digestibility of LCB.